Biological activity of the derivatives of 1,2,4-triazole - T. V. Kravchenko; O. I. Panasenko; E. G. Knysh (The State Expert Center of the Ministry of Health of Ukraine, 2018)
The rapid development of modern medicine and pharmacy leads to an increase in synthetic drugs. Thus, in the professional literature says that one of the perspective directions are searching for new biologically active compounds including heterocyclic systems and the introduction of the latest in medical, pharmaceutical or veterinary practice. It is known that heterocyclic ring system 1,2,4-triazole moiety is promising for the synthesis of new active ingredients with various kinds of pharmacological actions. The aim of the study was the analysis of literature and patent sources over the past 10 years and the generalization of the results for certain types of biological activity of 1,2,4-triazole. Results of literary analysis show a wide range of biological activity of 1,2,4-triazole-3-tion. The data determine the relevance of further research of derivatives of 1,2,4-triazole in the actoprotective, antimicrobial, antifungal, antihypoxic, hypoglycemic, analgesic, antiinflammatory and others activity in order to find new highly effective in terms of biological substances that can form the basis of new medicines.